TASAWUF DI WILAYAH PERKOTAAN: STUDI KASUS PENGAJIAN GURU YADI DI KOTA BANJARMASIN, KALIMANTAN SELATAN - Ridha Risda Yanti (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2019)
Abstract: In South Kalimantan, there are many tasawuf study groups, including the open and the secretive ones. This article discusses one example of secretive tasawuf study group located in Banjarmasin, the capital of South Kalimantan. The main focus is on the tasawuf teachings and practices of a man called Guru Yadi. To reflect on some sufi teachings, members of this study group practice some rituals unsual to other tasawuf study groups, namely, immersing their bodies in a pool filled with water and ice, laying down in a coffin to reflect on death, and sitting in an area where masquuitoes are plenty, training themselves of contentment. In addition to death reflection and contentment training, the main teachings of this study group are repentance, donation-making, and treating others nicely. Istigfar is a compulsory sacred recitation for the members, beside a variety of sholawat and Surah al-Ikhlas, before they start the above rituals. Based on my observation, this study group develops a falsafi-cum-akhlaki type of tasawuf. Abstrak: Di Kalimantan Selatan, terdapat banyak pengajian-pengajian tasawuf, baik yang terbuka maupun yang rahasia (sirr). Artikel ini mendiskusikan salah satu contoh pengajian tasawuf sirr yang berlokasi di Kota Banjarmasin. Pembahasan di sini meliputi ajaran dan praktek tasawuf asuhan seorang yang dikenal sebagai Guru Yadi. Untuk meresapi ajaran tasawuf, di pengajian ini ada sejumlah praktek yang tidak biasa, misalnya, menghilangkan rasa dengan berendam di kolam es, merenungi kematian dengan berbaring di peti mati, dan duduk tafakkur sambil melatih ikhlas di tempat yang banyak nyamuk. Selain mengingat mati dan melatih ikhlas, ajaran pokok lainnya dalam pengajian ini adalah bertaubat, bersedekah dan berbuat baik dengan sesama makhluk. Istigfar menjadi bacaan wajib bagi semua anggota jamaah pengajian ini, selain bermacam sholawat dan surah al-Ikhlas, sebelum mereka melaksanakan semua praktek di atas. Berdasarkan pengamatan saya, corak tasawuf yang dikembangkan di pengajian ini adalah falsafi dan akhlaqi.